Kemampuan Ibu dalam Memberikan Stimulasi Perkembangan pada Bayi Usia 0-2 Tahun Dengan Media Flashcard - Aida, Dinda Nur; Mansur, Herawati (Malang Journal of Midwifery (MAJORY), 2019)
Efforts to prevent developmental delays are by increasing the ability of mothers to stimulate their baby's development with flashcard media. This study aims to determine the effect of flashcard media on mothers' ability to provide developmental stimulation in infants aged 0-2 years. Pre-Experimental research design with One Group Pretest-Postest research design. The population was 20 people and used a total sampling technique with a sample size of 20 respondents. Data obtained from observation sheets. The results showed that respondents experienced increased ability after being given education with flashcard media. Data were analyzed using Wilcoxon Signed Rank Test statistical analysis. The results showed there was an influence of the flashcard media on the mother's ability to provide developmental stimulation in infants aged 0-2 years (? value <0.001). This flashcard media can be used as a guideline in providing more precise and directed development stimulation so that the baby's development period can be more optimal. Keywords: Development, Flashcard Media, Stimulation, Infant